PETROLOGY, GEOCHEMISTRY AND TECTONICAL ENVIRONMENT OF THE SHALAIR METAMORPHIC ROCK GROUP AND KATAR RASH VOLCANIC GROUP, SHALAIR VALLY AREA, NORTHEASTERN IRAQ - Awadh, Salih; Kettanah, Yawooz (Iraqi Journal of Science, 2024)
The Shalair Metamorphic Rock Group (SMRG) is northern exposure of variety lithological units in Iraq, and forms part of the western margin of the active Iranian plate. The SMRG consists of metasedimentary sequences, whereas the Katar Rash Volcanic Group (KRVG) consists of basic to acidic metaigneous rocks. The petrological and geochemical studies showed that the SMRG is characterized by three lithological units, these are metapelite, metacarbonate, metaarenite, and KRVG is characterized by metaigneous series including metabasalt, metaandesite, and metarhyolitic dacite. All these rocks are regionally metamorphosed into low grade metamorphism of green schist facies – chlorite zone. Thermal conditions of metamorphism are suggested about 340±20° C at pressure conditions ranged between 2.5 – 3 Kb approximately. Data is not completely enough to interpret the tectonical environment, but the field aspects and geochemical evidences indicate that the SMRG were evolved under tectonic environment of island arc situation, so the (KRVG) are characterized by calc – alkaline nature.